PENDIDIKAN INKLUSI PERSPEKTIF PENDIDIKAN ISLAM - Utomo, Budi; Assayyidi, Nurochman; Fikri, Ahmad Kamalul (MAMBA'UL 'ULUM, 2024)
The aim of this research is, firstly, to find out about inclusive education. Second, to find out about inclusive education from an Islamic perspective. Third, to find out about the implementation of inclusive education in Islamic education. This research uses library research methods (Library Research). Because this research includes library research, in collecting data, the method used is the documentation method, namely searching and extracting data from reading materials related to the problem. After the data was collected, the author then clarified and divided it into several chapters and sub-chapters according to their nature, in order to make it easier to answer the problem formulation. Based on the research results, it can be concluded that inclusive education will not be successful without community support and participation. Children with special needs will want to go to regular schools or even segregated schools only if they are supported by their parents and the community. Stakeholders can support schools with support in the form of facilities, infrastructure, learning aids, costs, technical support, and providing employment opportunities for graduates who meet the requirements. In the Islamic view, it really emphasizes the importance of education without distinguishing between humans. The obligation to seek knowledge is not limited to certain groups or groups, but is mandatory for all followers of Islam, whether male, female, disabled or normal.